News and Information Dispersion at Social Media and its Impact on Firms - Salamah, Fai M. Bin (International Journal of Advanced Science and Technology, 2020)
In current times, social media has become a prominent platform for news and information dissemination across the world. Due to this, good or bad news spread at social media within a short period of time affecting a firm’s reputation. Social media has become immensely popular because people get an opportunity to interact with others and inform them of their views almost free of cost. Some of the findings reveal that people from the younger generation, being more active at social media, get influenced easily by a variety of news and information that spread through social media. The research study is aimed at exploring how people at Kuwait County use social media for obtaining information; how some of the demographic factors such as age, gender, and education influence these people in relation to the news of a firm at social media. The study reveals that there is a strong correlation between trust in social media and its impact on the attitudes of people. Therefore, firms need to be extremely careful about the news and information posted on social media concerning them. It becomes imperative for them to see that issues are resolved within the appropriate time frame, especially during crisis times so that their reputation is not adversely affected.